Economic Development in Africa 2007 - United Nations Conference on Trade; Development (United Nations, 2007)
The 2007 Report examines domestic resource mobilization for growth and poverty reduction in African countries. It analyses how African countries can increase domestic resources and channel them into productive investments. The Report also examines how African countries can reclaim development “policy space”, and give true meaning to, “ownership” of development strategies that respond to their own priorities within the framework of a “developmental State”.